2012
DOI: 10.2119/molmed.2011.00357
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperglycemia Exacerbates Burn-Induced Liver Inflammation via Noncanonical Nuclear Factor-κB Pathway Activation

Abstract: Hyperglycemia and inflammation are hallmarks of burn injury. In this study, we used a rat model of hyperglycemia and burn injury to investigate the effects of hyperglycemia on inflammatory responses in the liver. Hyperglycemia was induced in male Sprague-Dawley rats with streptozotocin (STZ) (35-40 mg/kg), followed by a 60% third-degree scald burn injury. Cytokine levels (by multiplex, in cytosolic liver extracts), hormones (by enzyme-linked immunosorbent assay [ELISA], in serum), nuclear factor (NF)-κB protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Another consideration relates to the need to have a burn injury model of sufficient magnitude to cause hypermetabolism observed in human burns with high TBSA. During the early post-burn phase in humans, hyperglycemia occurs as a result of an increased rate of glucose appearance along with an impaired tissue extraction of glucose, leading to an overall increase of glucose and lactate [67]. Therefore, while the rat burn model is superior to the mouse in its ability to recapture hypermetabolism, it becomes complex when one tries to incorporate an infection feature to this model to replicate the post-burn sepsis seen in patients with greater than 60% TBSA.…”
Section: Standardized Scalding Burn Model In Ratmentioning
confidence: 99%
“…Another consideration relates to the need to have a burn injury model of sufficient magnitude to cause hypermetabolism observed in human burns with high TBSA. During the early post-burn phase in humans, hyperglycemia occurs as a result of an increased rate of glucose appearance along with an impaired tissue extraction of glucose, leading to an overall increase of glucose and lactate [67]. Therefore, while the rat burn model is superior to the mouse in its ability to recapture hypermetabolism, it becomes complex when one tries to incorporate an infection feature to this model to replicate the post-burn sepsis seen in patients with greater than 60% TBSA.…”
Section: Standardized Scalding Burn Model In Ratmentioning
confidence: 99%
“…The subsequent hyperglycemia is associated with increased mortality and infectious complications in pediatric burn patients [34] and a prospective analysis of 152 burn patients demonstrated found decreased rates of pneumonia, ventilator-associated pneumonia, and urinary tract infection infections with tight glycemic control [35]. Hyperglycemia also aggravates burn-induced liver inflammation via activating nuclear factor-κB (NF-κB) signaling in hepatocytes as demonstrated in a rat model [36]. Alcohol consumption can have paradoxical effects on plasma glucose levels depending on the setting.…”
Section: Extrahepatic Mechanismsmentioning
confidence: 99%
“…During the early phase of postthermal injury, patients experience hyperglycemia as a result of the catabolic state and hormonal environment that favors glucose appearance along with impaired glucose extraction by tissues 72 , 73 . This hyperglycemic state following burn injury can be detrimental and can lead to adverse outcomes in these patients if not controlled and resolved swiftly 38 , 74 , 75 . Studies have shown that burn patients with poor glucose control experience a significantly higher incidence of infections and mortality compared with burn patients with good glucose control 39 , 74 , 75 .…”
Section: Pharmacologic Modalities In Alleviating the Postburn Patholomentioning
confidence: 99%
“…Following this primary goal, nutrition support is used to alleviate and modulate the postburn catabolic and pathological responses of hypermetabolism, immunosuppression, and disturbed wound healing. Despite the obvious need for nutrition support in these patients, the supply of excess nutrition in the form of carbohydrates and fat can result in hyperglycemia and fat infiltration of organs 37 39 . Currently, no standardized nutrition support guidelines exist for burn patients.…”
Section: Nutrition Support In Alleviating the Postburn Pathological Amentioning
confidence: 99%
See 1 more Smart Citation